(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2006)
The calcareous nannofossil content of the Toarcian succession, widespread in the Lusitanian Basin (Central Portugal), has been studied on the basis of a closely spaced sampling and a refined lithostratigraphic frame dated by ammonites. The almost continuous calcareous nannofossil record allows to calibrate the biohorizons and zone boundaries (NJ5/NJ6, NJ6/NJ7 NJ7/NJ8) with respect to the ammonite zones, and to characterize Toarcian nannofossil zones. The easily recognizable events include the LCO of Calcivascularis jansae (Levisoni Zone), the FOs of Carinolithus cantaluppii and Carinolithus superbus (Levisoni Zone), the FO of Discorhabdus striatus (Bifrons Zone), the AE of Lotharingius hauffii (Gradata Zone) and the FO of Watznaueria contracta (Aalensis Zone). The other events are helpful to increase the resolution, albeit they are defined by taxa with a low abundance and discontinuous occurrence. They comprise the LOs of Biscutum grande and Biscutum finchii (Levisoni Zone) and the FOs of Discorhabdus criotus (Gradata Zone), Retecapsa incompta (Bonarelli Zone) and Triscutum sullivanii (Speciosum Zone). Both biohorizons and zone boundaries are compared with previous findings from the Basque-Cantabrian area and Iberian Range (Spain) as well as from NW Europe and Italy/S France.